MINORS ON TRIAL FOR CRIME: VIEW OF THE CHILD PSYCHIATRIST IN JUDICIAL ENVIRONMENT IN BENIN - Anagonou, L; Ebo B, Houinou; Adeossi, F; Klikpo, E; Salifou, S; Gbetogbe, K; Gansou, Gm; Kpadonou E, Fiossi (International Journal of Research -GRANTHAALAYAH, 2020)
The developmental path of the minor may be marked by particular situations such as conflicts with the law, various crimes. The situations, contexts and processes that lead to crime are multiple. Thus, the aim of our research was to study the characteristics of minors judged for crime, seen in a judicial space. This was a retrospective, cross-sectional, descriptive study carried out at the Cotonou First Instance Court. Data were collected from the judicial files of minors tried for crime by the juvenile court ruling on criminal matters from 1 January 2011 to 31 December 2015; 34 files were taken into account. The respondents were all adolescents aged between 10 and 18 years. The majority of them were tried for homicide (61.7%) and rape (32.4%). For 35.3% of the minors tried for crime, the relationship with opposite sex parent had poor quality. These minors received a firm prison sentence (88.2%), and 11.8% of them were placed in a foster centre without receiving a prison sentence. Crimes committed by minors calls into question our ability to supervise and provide a safe and appropriate framework for the psychological construction of children and adolescents in our society. Measures should be taken in terms of prevention at various levels to reduce the risk of children developing criminal behaviour.